Cognitive energizer - Qamaruz Zaman, Faridah; Yaacob, Muhammad; Rahmat, Mohd Hafizad; Zamzuri, Azmir (University Putra Malaysia, 2012)
Every perfume has three components: top notes, middle (heart) notes and base notes. The top notes are the first notes to warm and dissipate; they are the first fragrance that you smell. This lasts for 5-10 minutes. The fragrances are light and fresh. The middle (heart) notes represent the body of the perfume. They last for 10-60 minutes. These smells are stronger and heavier than the top notes. The bottom (base) notes are long-lasting (1-24 hours) and heavy. The three parts combine like a symphony.